The Relationships of Modifiable Risk Factors with Hypertension Client Recurrence Prevention Behaviors - Ibnu, Faisal; Hidayati, Rina Nur (Jurnal Keperawatan Respati Yogyakarta, 2025)
Hypertension is still a major problem in the world, both in developed countries and in developing countries, including Indonesia. The number of people with hypertension continues to increase every year, it is estimated that by 2025 there will be 1.5 billion people affected by hypertension, and it is estimated that every year 10.44 million people die from hypertension and its complications. The prevalence of hypertension in Indonesia from year to year tends to increase. This study uses a correlational analytical design with a case-control approach. The population in this study is all hypertension clients in the working area of the Bangsal Health Center. The sample was taken from a part of the population that met the criteria with a purposive sampling technique of 58 respondents. The results of the study showed that the risk factors that affected the prevention behavior of hypertension clients in Pacing village, the working area of the Bangsal Mojokerto Health Center were physical activity, fruit and vegetable consumption habits, smoking habits, and alcohol consumption habits. Where the factors that most affect the prevention behavior of hypertensive clients are physical activity factors with a Correlation value of 0.646 and a p-value of 0.000. Hypertensive clients should be willing to do physical activity in daily life and the importance of increasing fruit and vegetable consumption and being able to reduce the habit of consuming cigarettes and alcohol.